New information on the breeding biology of fifteen Brazilian bird species - Gussoni, Carlos Otávio Araujo; Gomes, Arthur Monteiro; Perrella, Daniel Fernandes; Guaraldo, André de Camargo; Machado, Rogério Carlos; Tinti, Maria Clara; Paixão, Paloma Hokama; Noventa, Helbert Eduardo; Rodrigues, Vítor André; Rampin, Sidinei (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2023)
Although birds are a well-studied group, the breeding biology of many species is still poorly known, especially in the Neotropical region. This lack of knowledge implies the absence of subsidies for conservation, lack of more reliable data for phylogenetic reconstruction, and for studying the effects of environmental change on these species. In view of this scenario we collected information on the reproduction of 15 bird species in 16 Brazilian locations from February 2003 to December 2021. This article presents new data on the nests, eggs, juveniles/nestlings and/or breeding behavior of Veniliornis spilogaster (Picidae), Philydor atricapillus (Furnariidae), Myiobius barbatus (Onychorhynchidae), Tityra semifasciata (Tityridae), Phylloscartes paulista (Rhynchocyclidae), Phylloscartes oustaleti (Rhynchocyclidae), Elaenia obscura sordida (Tyrannidae), Tyrannus albogularis (Tyrannidae), Cnemotriccus fuscatus (Tyrannidae), Icterus pyrrhopterus (Icteridae), Nemosia pileata caerulea (Thraupidae), Trichothraupis melanops (Thraupidae), Thlypopsis sordida (Thraupidae), Cyanophonia cyanocephala (Fringillidae) and Chlorophonia cyanea roraimae (Fringillidae). We include new data on parental care for six species, descriptions of nests for eight species, and new information on nest building behavior for five species. This data is of special interest for the management of these species and their habitats and for the reconstruction of their phylogenetic relationships.
Keywords: Nest; Egg; Constancy of incubation; Juvenile; Parental care